Microstructure evolution and mechanical properties of as-rolled Mg-Al-Ca-Mn alloy sheet with Al2Ca phase and Mg2Ca phase - M.Q. Zhang; T. Nakata; C. Xu; G.Z. Tang; K.K. Deng; T. Liu; K. Cui; X.J. Wang; G.S. Wang; S. Kamado; L. Geng (Journal of Materials Research and Technology)
In this study, Mg-Al-Ca-Mn alloy sheets containing distinct Laves phases (Al2Ca phase and Mg2Ca phase) were fabricated via composition modulation and hot rolling to systematically investigate the microstructure evolution and mechanical properties. At the initial rolling stages, microstructure examination revealed that the {101¯2} tensile twin and the {101‾1}-{101‾2} double twin mainly occurred in the original grains, in which the Mg-1.0Al-3.0Ca-0.4Mn (wt.%) alloy with high {101‾2} tensile twin ratio exhibited broad transverse direction (TD)-split texture. With increasing accumulative reduction, the original grains with crystal orientation near [112‾0]//TD were gradually rotated to [101‾0]//TD around the [0001] axis, facilitating the in-situ conversion from sub-grains to dynamic recrystallized (DRXed) grains via the continuous DRX (CDRX) mechanism. Ultimately, the alloys exhibited a typical bimodal microstructure consisting of DRXed grains and un-DRXed grains. The micron-sized Al2Ca phases with high elastic modulus stimulated DRX by the particle stimulated nucleation (PSN) mechanism, leading to a moderate DRX ratio with 46 % for the Mg-5.0Al-2.0Ca-0.4Mn (wt.%) alloy. The nano-sized Guinier Preston (G.P.) zones and Al2Ca precipitates could effectively restrict the non-basal dislocation slips, resulting in a low DRX ratio with 21 % for the Mg-1.0Al-3.0Ca-0.4Mn (wt.%) alloy. Consequently, the alloy containing Al2Ca phase exhibited higher ductility than that containing Mg2Ca phase.